Educación a distancia y presencial en la formación de posgrado en enfermería tras la pandemia de CoVid-19 (Avances en Enfermería, 2023)
Over the past decades, postgraduate nursing education has maxi-mized the advancement of knowledge in health sciences around the world. Thanks to the modern pedagogical approaches and new higher education models that consider undergraduate —bachelor's degree, licentiate, or technological program— and graduate stu-dents —specialization, master’s, or doctorate courses— as the main protagonists of the education process, master's and doctorate pro-grams have allowed the generation of more technological products and high-impact scientific research. As a result, these graduate programs have gained more public, social, media, and cyberculture visibility. However, the CoVid-19 pandemic has raised questions regarding nursing education under these academic programs [Fragmento de texto]
Keywords: s:21:"Educación a Distancia"; s:36:"Educación de Postgrado en Enfermería"; s:9:"Enseñanza"; s:10:"Enfermería"; s:8:"COVID-19"